Konseling Individu Dengan Teknik Cognitif Restructuring Dalam Kekerasan Verbal Orangtua Terhadap Anak - Aini, Aini; Razzaq, Abdur; Jannati, Zhila (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Verbal violence is verbal action that has the effect of violence, either with words that are explicit in the surface structure or words that are implied in a deep structure that are carried out against other people by using words that can hurt other people. The purpose of this study was to find out the description of parental verbal abuse in children, to find out the application of individual counseling with cognitive restructuring techniques, to find out the factors that influence the occurrence of verbal violence in children, to know the description of parental verbal abuse in children after individual counseling with cognitive techniques was applied. restructuring. This type of research is a type of field (field research). Data analysis uses a qualitative method with a case study approach. Data collection tools are observation, interviews, and documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusions/verification. The subject of this research is client "A" in Serimbang Village. The results of this study indicate that verbal abuse by client "A" towards children is shown by calling the child's name inappropriately, belittling the achievements of the child, swearing at the child with harsh words, refusing in the form of neglect, threatening by using a sharp tool or object , threatening with physical hitting, blaming the child when there is a problem, and teasing the child when he makes a mistake. As for the factors that influence the occurrence of verbal violence, namely the low economy as well as communication between client "A" and the child which is the trigger for the occurrence of verbal violence against children, due to busyness and low economic situations and conditions causing client "A" to be stressed to the point of exhaustion due to the demands of work trigger emotional turmoil or unable to manage emotions and inability to deal with existing problem situations. Then there is a change in the client, namely the client can overcome negative thoughts into positive ones and can manage emotions or overcome existing problems without having to involve children and commit verbal violence against children with the situations and circumstances of the problems faced by parents.